Role of the inflammasome in insulin resistance and type 2 diabetes mellitus - Lu, Shen; Li, Yanrong; Qian, Zhaojun; Zhao, Tiesuo; Feng, Zhiwei; Weng, Xiaogang; Yu, Lili (Frontiers in Immunology, 2023)
The inflammasome is a protein complex composed of a variety of proteins in cells and which participates in the innate immune response of the body. It can be activated by upstream signal regulation and plays an important role in pyroptosis, apoptosis, inflammation, tumor regulation, etc. In recent years, the number of metabolic syndrome patients with insulin resistance (IR) has increased year by year, and the inflammasome is closely related to the occurrence and development of metabolic diseases. The inflammasome can directly or indirectly affect conduction of the insulin signaling pathway, involvement the occurrence of IR and type 2 diabetes mellitus (T2DM). Moreover, various therapeutic agents also work through the inflammasome to treat with diabetes. This review focuses on the role of inflammasome on IR and T2DM, pointing out the association and utility value. Briefly, we have discussed the main inflammasomes, including NLRP1, NLRP3, NLRC4, NLRP6 and AIM2, as well as their structure, activation and regulation in IR were described in detail. Finally, we discussed the current therapeutic options-associated with inflammasome for the treatment of T2DM. Specially, the NLRP3-related therapeutic agents and options are widely developed. In summary, this article reviews the role of and research progress on the inflammasome in IR and T2DM.